166 CLINICAL IMPACT OF NEW BIOMARKERS IN THE PATIENTS WITH ESOPHAGEAL CARCINOMA. (17th September 2021) - Shimada, Hideaki; Yajima, Satoshi; Oshima, Yoko; Nanami, Tatsuki; Ito, Masaaki; Suzuki, Takashi; Shiratori, Fumiaki; Hoshino, Isamu; Nabeya, Yoshihiro
Abstract: : We have developed several new biomarkers in patients with esophageal carcinoma. In this paper, we reviewed the clinical impact of serum autoantibodies, growth factors, blood counts, and other serum tumor markers. Methods: Blood samples of patients with esophageal carcinoma were obtained before surgery and were stored at −80°C until the ELISA assay. Target tumor antigens for autoantibodies were SURF1, LOC, HOOK2, AGENCOURT, TROP-2, TRIM21, GLUT-1, Myomegalin, Makorin-1, CUEC-23, ECSA-1, p53, and NY-ESO-1. Growth factor-related molecules were followed; midkine, VEGF, PDECGF, and HGF. The other markers were followed; platelet, CRP, IAP, SCC-Ag, CYFRA21-1, and fibrinogen. Results: A total of 24 biomarkers were evaluated for their clinical impact on patients' survival and tumor stages. High positive rates, more than 40% were found in SURF1, Myomegalin, midkine, and HGF. Although the majority of autoantibodies did not have a prognostic impact, all the growth factors have a prognostic impact on patients' survival. Lutine blood tests, such as platelet count, neutrophil-lymphocyte ratio, fibrinogen, and CRP, were also useful to predict prognosis. Conclusion: We have evaluated the clinical impact of 24 new biomarkers, including 13 autoantibodies, for the patients with esophageal carcinoma. Although the autoantibodies were useful to detect relatively early stage of the disease, the prognostic impact of these biomarkers was limited. All growth factors were useful to predict patients' survival.